Computationally efficient and quantitatively accurate multiscale simulation of solid-solution strengthening by ab initio calculation. (15th February 2015) - Ma, Duancheng; Friák, Martin; von Pezold, Johann; Raabe, Dierk; Neugebauer, Jörg
Abstract: We propose an approach for the computationally efficient and quantitatively accurate prediction of solid-solution strengthening. It combines the 2-D Peierls–Nabarro model and a recently developed solid-solution strengthening model. Solid-solution strengthening is examined with Al–Mg and Al–Li as representative alloy systems, demonstrating a good agreement between theory and experiments within the temperature range in which the dislocation motion is overdamped. Through a parametric study, two guideline maps of the misfit parameters against (i) the critical resolved shear stress, τ 0, at 0 K and (ii) the energy barrier, Δ E b, against dislocation motion in a solid solution with randomly distributed solute atoms are created. With these two guideline maps, τ 0 at finite temperatures is predicted for other Al binary systems, and compared with available experiments, achieving good agreement.